Application of WiMAX technology in difficult geographical conditions: Perspectives for mountain environment - Rustamova D. F.; Suleymanov N. M.; Gafarov G. A.; Bakhshaliyeva S. V.; Marasulov M.; Rizaeva Sh. (BIO Web of Conferences)
WiMAX (Worldwide Interoperability for Microwave Access) is a telecommunications technology designed to provide universal wireless communication over long distances for a wide range of devices (from workstations and notebook computers to mobile phones). It is based on IEEE 802.16 standard called Wireless MAN. The name “WiMAX” was coined by the WiMAX Forum, which was established in June 2001 to promote and develop WiMAX technology. The forum describes WiMAX as “a standards- based technology that provides high-speed wireless network access as an alternative to leased lines and DSL.” WiMAX allows you to access the wireless Internet at high speed with a wider coverage than Wi-Fi networks. This allows the technology to be used as “backbones”, a continuation of traditional DSL and leased lines, as well as local networks. As a result, this approach makes it possible to create high-speed networks that expand across cities. In recent years, the development of network technologies has led to a significant expansion of the list of possible ways of connecting personal computers to the network and the types of connections to the global Internet. From a server to a pocket computer, almost any personal device that has enough computing power to process text and graphic information is equipped with one or another network interface, from a modem to WiMAX. This article examines the application of WiMAX technology in mountainous conditions, and analyzes the technical solutions used to create a continuous and high-quality connection despite topographical and environmental challenges. The advantages of wireless communication technologies are shown in mountainous areas where the population is small and the infrastructure is limited. The article presents strategies for configuring WiMAX networks, installing base stations, and expanding network coverage. As a result, WiMAX is proving to be an effective solution for meeting broadband communication needs in mountain environments.